Fibrin Clot Strength in Patients with Diabetes Mellitus Measured by Thrombelastography - Benjamin T. Maatman; Glen Schmeisser; Rolf P. Kreutz (Journal of Diabetes Research)
Background. Patients with diabetes mellitus (DM) exhibit increased risk of recurrent myocardial infarction. Maximal clot strength measured by thrombelastography (TEG) is a risk factor for recurrent ischemic events. We hypothesized that diabetic subjects exhibit increased fibrin clot strength in platelet-poor plasma and that glycemic control correlates with maximal fibrin clot strength. Methods. We collected plasma samples from subjects with known or suspected coronary artery disease undergoing cardiac catheterization (n=354). We measured kaolin-activated TEG in platelet-poor citrate plasma. Time to fibrin formation (R), clot formation time (K), and maximal fibrin clot strength (MA) were recorded. Results. Plasma fibrin MA was increased among subjects with DM (n=152) as compared to non-DM (n=202) (37.0 ± 8 versus 34.1 ± 8 mm; p<0.001). Hemoglobin A1c (HbA1c) (ρ=0.22; p=0.001) and fibrinogen (ρ=0.29; p<0.001) correlated with fibrin MA. In multivariable regression analysis, DM remained significantly associated with plasma MA after adjustment for fibrinogen level (p=0.003). Conclusions. Subjects with diabetes mellitus exhibit increased maximal fibrin clot strength measured by TEG in platelet-poor plasma.